Study on coupling coordination and regional characteristics of “explicit-implicit” patterns in cultivated land use in Northeast China - Wang, Ning; Ning, Jing; Sun, Yu; Wang, Mengqiu; Ma, Haozhi (Frontiers in Environmental Science, 2025)
In the new era of “trinity” high-quality coordinated development, clarifying spatiotemporal pattern of cultivated land use patterns (CLUP) and classifying their regional types can provide a scientific basis for establishing a differentiated governance model in Northeast China that balances quantity control, quality improvement, and ecological conservation. Based on the analytical framework of two-dimensional coupling and dynamic mutual feedback between the explicit pattern of cultivated land use (EPCLU) and implicit pattern of cultivated land use (IPCLU), this study comprehensively applies the entropy weight method, coupling coordination degree model, and kernel density estimation method to systematically analyze the spatial differentiation, coupling characteristics, and evolutionary trends of CLUP in Northeast China from 2000 to 2020. Additionally, it adopts a multi-dimensional grade coupling classification method based on two-dimensional threshold determination to identify the regional types. The results show that: (1) The cultivated land use system in Northeast China demonstrates a coordinated evolution feature, featuring stable improvement of the EPCLU and stage-specific leaps of the IPCLU. (2) The coupling coordination level of the regional “EPCLU-IPCLU” has increased continuously, developing toward a more coordinated and efficient state, while the feature of single-pole concentration remains notable. (3) Five regional types are identified: Comprehensive Significant Type (CST), Explicit Dominant Type (EDT), Implicit Dominant Type (IDT), Comprehensive Weak Type (CWT), and General Development Type (GDT). The spatial patterns and progression trends of these types are jointly driven by natural background, policy adjustment, and technology-market elements. The research results can provide a reference for the optimal allocation and sustainable development of cultivated land resources under the background of high-quality development.